Comparing the difference in enhancement of kokumi-tasting γ-glutamyl peptides on basic taste via molecular modeling approaches and sensory evaluation - Juan Yang; Jing Guo; Ruijie Mai; Hao Dong; Chun Cui; Xiaofang Zeng; Weidong Bai (Food Science and Human Wellness)
γ-Glutamyl peptides can enhance basic taste sensations such as saltiness, sweetness, and umaminess, while the molecular mechanism and the difference in taste enhancement remain elusive. Thus, two complex conformations: taste type 1 receptor 1 (T1R1)-MSG and taste type 1 receptor 2 (T1R2)-sucrose were constructed to form binding receptors. These peptides showed affinity for the two receptors, but a higher affinity scores and more binding amino acid residues for the T1R1-MSG receptor, implying that they may exhibit a higher umami-enhancing effect. Thereinto, γ-glutamyl alanine (γ-EA) displayed the highest affinity for the two receptors through mobilizing multiple amino acid residues to form hydrophobic and hydrogen bonds, indicating it had the highest enhancement for umaminess and sweetness among these peptides. Sensory evaluation demonstrated the enhancement of γ-EA on umaminess was superior to that of sweetness. Generally, γ-glutamyl peptides could enhance basic taste sensation via activating taste receptor, and exhibited a highest umami-enhancing effect.